A differentiation protocol for generating pancreatic delta cells from human pluripotent stem cells - Zhang, Tongran; Wang, Nannan; Liao, Zhiying; Chen, Jingyi; Meng, Hao; Lin, Haopeng; Xu, Tao; Chen, Lihua; Zhu, Ling-Qiang; Liu, Huisheng (Frontiers in Cell and Developmental Biology, 2024)
In this protocol, we detail a seven-stage differentiation methodology for generating pancreatic delta cells (SC-delta cells) from human pluripotent stem cells (hPSCs). In the first step, definitive endoderm is generated by activin A and CHIR99021, followed by induction of primitive gut tube and posterior foregut by treatment with FGF7, SANT1, LDN193189, PdBU and retinoic acid (RA). The subsequent endocrine generation and directed SC-delta cell induction is achieved by a combined treatment of the FGF7 with FGF2 during stage 4 and 5, together with RA, XXI, ALK5 inhibitor II, SANT1, Betacellulin and LDN193189. The planar cultivation is converted to a suspended system after stage 5, allowing cells to aggregate into delta cell-containing spheroids. The differentiation takes approximately 4-5 weeks for delta cell generation and an additional 1-2 weeks for cell expansion and evaluation. We believe that this amenable and simplified protocol can provide a stable source of SC-delta cells from efficient differentiation, facilitating further investigation of the physiological role of delta cells as well as refinement of islet cell therapeutic strategies.